Integrate the procedures of textual analysis of the poetic image Between rhetoric and stylistic - tarrouche, hocine (Al-Adab Journal, 2021)
The general aim of this intervention is to highlight the positive aspect of Arabic eloquence by comparing it to the methodical science that claims to be scientific and objective. At the same time, the personal and superficial rhetoric is accused by an important structural element of literary composition, the poetic image. I chose the poetic picture because it is regarded in the eyes of rhetoric and stylistic as a linguistic composition based on the imagination, understanding and interpretation cannot go beyond the linguistic boundaries, which is an important way to combine the two sciences separated time and environment and brought together many procedural tools born in the hands of rhetoric and developed between the folds Stylistics.